RANCANG BANGUN EMERGENCY DEVICE UNTUKPENDAKI GUNUNG DENGAN TEKNOLOGI LONG RANGEBERBASIS ESP32 TERINTEGRASI TELEGRAM - FAWAZ NAWFAL, (2024)
Problems that may arise when mountain climbing can be fatigue, getting lost and illness. According to data from BNPB, 23 mountain climbers died as a result of being trapped when Mount Marapi erupted on December 3, 2023. According to data from BASARNAS, accidents in mountaineering have increased in the last four years. From these problems, an emergency communication tool is needed that can send emergency signals. This research uses components such as ESP32, GPS UBlox Neo-M8, LoRa Ra-02 and Telegram as a database. This tool can send the coordinates of the climber's location to the rescue team with the telegram application. Based on the research results, the tool is able to send signals up to 450 meters. For the highest average GPS accuracy value is 1.25 meters while the lowest average GPS accuracy is 15.24 meters, the best average RSSI is at -56.40 dBm when 0 meters far away, while the worst average RSSI is at -89.80 dBm when 110 meters far away, the lowest packet loss value is 1% and the highest packet loss is 19%. Hopefully with this emergency communication tool can help the rescue team in evacuating mountain climbers who experience accidents in the mountains.